Celtis flumeniana (Cannabaceae): a new species from Brazil and reestablishment of Celtis alnifolia - Zamengo, Henrique Borges; Gaglioti, André Luiz; Pederneiras, Leandro Cardoso (Phytotaxa, 2023)
During taxonomic studies of the Neotropical region, we recognized morphological differences that allowed us to reestablish Celtis alnifolia and describe a new species of Celtis from Brazil. For this new species, we provide its taxonomic description, a distribution map, and a preliminary analysis of its conservation status.